Al-Ittijah al-Ṣūfī wa al-Adab al-Sāmī fī al-Adab al-Indūnīsī al-Mu’āṣir - Nursomad, Nursomad (Studia Islamika, 1999)
The article is a study on the strength of the sûfi elements in modern Indonesian literary discourse.  Having explored the discourse on Sufism in the works of literature by the sûfi poets mentioned above,  the article discusses the socio-political and religious  context in which this transcendental  literature emerged. And in this case there are at least twoDOI: 10.15408/sdi.v6i3.726